2021
DOI: 10.1177/03000605211002703
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of testicular sperm retrieval in patients with non-obstructive azoospermia: a review

Abstract: Azoospermia is divided into two categories of obstructive azoospermia and non-obstructive azoospermia. Before 1995, couples with a male partner diagnosed with non-obstructive azoospermia had to choose sperm donation or adoption to have a child. Currently, testicular sperm aspiration or micro-dissection testicular sperm extraction combined with intracytoplasmic sperm injection allows patients with non-obstructive azoospermia to have biological offspring. The sperm retrieval rate is significantly higher in micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
2
4
0
Order By: Relevance
“…We studied factors that can predict successful sperm retrieval in men with NOA. It was determined that older men had a higher likelihood of successful sperm retrieval, consistent with a study by Ramasamy, 12 but in contrast to another studies 13 . The triad of testicular volume, FSH, and testosterone levels were not predictive of successful sperm retrieval and this finding supports previous research, 13 suggesting that the focal distribution of spermatogenesis may play a role in this phenomenon, rather than a global distribution.…”
Section: Discussionsupporting
confidence: 85%
“…We studied factors that can predict successful sperm retrieval in men with NOA. It was determined that older men had a higher likelihood of successful sperm retrieval, consistent with a study by Ramasamy, 12 but in contrast to another studies 13 . The triad of testicular volume, FSH, and testosterone levels were not predictive of successful sperm retrieval and this finding supports previous research, 13 suggesting that the focal distribution of spermatogenesis may play a role in this phenomenon, rather than a global distribution.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, spermatozoa can be retrieved from testicular tissue in only about 50% of cases [5,6]. Some teams have aimed to identify the most predictive factors of a positive TESE, first using univariate models, followed by multivariate models and, finally, artificial intelligence, including machine learning (ML) models [7]. We conducted a scoping review on the prediction of TESE success, extended to relevant citations on PubMed (MeSH terms: TESE; prediction; non-obstructive azoospermia; machine learning; sperm).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a history of cryptorchidism and smoking status have shown inconsistent results [27][28][29]. Consequently, separately, none of these predictors has so far shown satisfactory, sufficient, and reproducible predictive performance to guide practitioners regarding the probability of TESE success and the evaluation of the benefit-risk balance [7,14,[30][31][32][33]. In addition, this surgery involves a substantial cost for some patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have confirmed that neither FSH nor testicular volume can be used as an independent predictor. 4 , 5 At the same time, although diagnostic testicular pathology helps predict the success rate of micro-TESE, it is difficult to use it as an independent predictor in KS patients with small testes. 6 In recent years, an increasing number of researchers have focused on the use of anti-Müllerian hormone (AMH) to evaluate male spermatogenic function and predict the outcome of sperm extraction, and a consensus for the application value of AMH has not yet been reached.…”
Section: Introductionmentioning
confidence: 99%